A multidimensional strategy: ways to combat cyclic vomiting syndrome with hiatus hernia and gastroesophageal reflux disease in a young adult female - Gullaam Rasul, Siti Faezah; Draman, Nani; Mat Yudin, Zainab; Jamani, Nurjasmine Aida; Mustaffa, Nazri (International Islamic University Malaysia, 2023)
Cyclical vomiting syndrome (CVS) is a chronic idiopathic functional gastrointestinal disorder characterised by intermittent episodes of severe nausea and vomiting with symptoms-free intervals in between. CVS is seen in various age groups with a prevalence of 1.9%. Numerous psychosocial, physical and infectious stressors have been attributed as a trigger of CVS. Often, a co-existing organic and psychiatric comorbidities mask the disorder, and an absence of diagnostic investigation causes a delay in diagnosis and makes it challenging to treat.